International Exchange: A Foundation for Theory Building in International Business - Toyne, Brian (Journal of International Business Studies, 1989)
There does not appear to be a consensus concerning what is the conceptual domain of international business. This paper argues that this is due in part to an emphasis on the firm as the unit of analysis. It is further argued that a comprehensive, generative and theoretically integrative definition of international business could be established if exchange were made the unit of analysis. By using the political economy paradigm and the various concepts of exchange adopted by the social sciences, nine characteristics are identified and developed which uniquely define the conceptual domain of international business.